AB0478 Comparative study between patients with normal and overweight in a cohort of systemic lupus eritemathosus from argentina. (15th June 2017) - Beron, AM; Duran, S Sapag; Carrasco, M Garcia; Duran, AM Sapag; Medina, G; Nasswetter, G; Dubinsky, D
Abstract : Background: Systemic lupus erythematous (SLE) have an increase cardiovascular risk, worsened by overweight and obesity. Increased BMI is associated with other severe complications and comorbidities as lupus nephritis, hypertension, insulin resistance and dyslipemia. Body weight is a modifiable risk factor. Objectives: To determine the frequency of overweight and obesity in patients with SLE and their impact on this disease Methods: Descriptive, cross-sectional study. We reviewed the medical records of outpatients with SLE (ACR 1997) who were seen since 2014 to 2016 in the Clinical Hospital of Buenos Aires, Argentina. We evaluated sex, age, disease duration, obstetric history, use and doses of oral corticosteroids, BMI, 25 OH vitamin D and educational level. Disease activity was scored by SLEDAI. Scores ≥4 were classified as active. The patients were classified into 2 groups, according to BMI: normal weight (NW) (19–25), overweight and obesity (≥25). Results: One hundred and sixty two of 230 were evaluated. Sixty-eight patients were excluded due to lack of data. 157 (97%) were women. Mean age for both sexes was 40.6±14.3 years (p 0.70). Means of: SLEDAI 4.3±4.47 (54.9% had SLEDAI ≥4), IMC: 27.04±5.22 (56% had a BMI ≥25) and 25-hidroxivitamin D was 25.15±9.0. Relation between 2 groups, according to BMI: 84.5% whom were in NW group have received steroids at some point vs 95.6% in BMI≥25 group (p 0.02). Mean steroids doses: BMI ≥25: 9.53±10.98 vs 5.0±7.2 in NW group (p 0.04). Multivariate analysis showed that BMI ≥25 continued significantly associated with SLE duration, independently of the steroids use and other variables. 25 OH vitamin D tended to be lower in BMI ≥25 vs NW, but no significant differences (24.53±9.91 vs 25.50±9.85) (p=0.071) Conclusions: Over a half of our cohort had BMI ≥25 and was characterized by older age, more frequent menopause, longer course of the disease, increased steroid use and lower educational level. Depression and hypertension were the statistically more frequent comorbidities found. Obesity was associated with more activity and accrual damage including chronic renal disease. Disclosure of Interest: None declared